EFL Pre-service Teacher’s Teaching Anxiety and the Coping Strategies during Teaching Practicum - Khofifah Novitasari; Banatul Murtafi'ah (Journal of English Education and Teaching, 2022)
This research aims to investigate the sources of teaching anxiety as experienced by EFL pre-service teachers during the teaching practicum and the types of strategy used to cope with the teaching anxiety. This research used Aydin (2016) and Murray-Harvey et al. (2000) frames to investigate the sources of teaching anxiety and the strategies to cope with it. One English pre-service teacher was willing to participate as participant in this research. The data were collected through semi-structured interviews. The researchers found that the pre-service teacher was anxious mostly due to the lack of teaching experience, her personality, fear of making mistakes, difficulties in time management, lack of learner motivation, and technical issues. This research revealed that there are eight strategies used by the participant to cope with her teaching anxiety (i.e., cognitive strategies, behavioral strategies, emotional strategies, self-management skill, professional qualities, discussion with people, support from supervising teacher, and feedback from lecturer supervisor). Further implications and recommendations are also described in this research. The results from this research suggest alternatives for EFL pre-service teachers to cope with anxiety during teaching practicum.